Job loss by wage level: Lessons from the Great Recession in Ireland - Brian Nolan; Sarah Voitchovsky (IZA Journal of European Labor Studies, 2016)
This paper explores the incidence of job loss by wage level during the Great Recession, using data for Ireland. Ireland experienced a particularly pronounced decline in employment by international and historical standards, which makes it a valuable case study. Using EU Survey on Income and Living Conditions (EU-SILC) data, our analysis reveals that the probability that an employee remains in employment, from one year to the next, is positively related to their monthly earnings during both boom and bust. The gradient with wages, however, is much more marked during the bust and remains significantly so even after controlling for a range of individual characteristics including gender, age, education, labour market history, part-time status, industries or occupations.
Keywords: E24; J23; J24; J62; J63; 330; Skills; Occupations; Wages; Great recession; Ireland; Job loss; EU-SILC; Kündigung; Lohnniveau; Qualifikation; Arbeitslosigkeit; Weltwirtschaftskrise; Irland